Forest management plans as data source for the assessment of the conservation status of European Union habitat types - Alterio, Edoardo; Campagnaro, Thomas; Sallustio, Lorenzo; Burrascano, Sabina; Casella, Laura; Sitzia, Tommaso (Frontiers in Forests and Global Change, 2023)
Natura 2000 is a European network of protected sites that should enable natural habitats to be maintained or restored at a favorable conservation status. Progress toward this objective must be periodically reported by states members of the European Union. We investigated how forest management plans might provide data to support the reporting. The study was done in the forests of the Dolomites and Venetian Prealps, Italy. Here, about 200 forest management plans, divided into several forest compartments, have been drawn up and revised every 10–15 years. Stand structure variables were retrieved from past (OR, 1970–1980) and more recent revisions (NR, 2000–2010) of 331 forest compartments ranging between 0.35 and 53.1 ha. In the beech and spruce forest habitat types (coded 9130 and 9410 in Annex I of the Directive 92/43/EEC, respectively), we found an increase from OR to NR in the density of large trees (from 32 to 46/ha and from 31 to 50/ha, respectively for the two habitats), basal area (from 27.3 to 31.5 m2/ha and from 31 to 34.5 m2/ha), mean diameter (from 34.1 to 36.2 cm and from 33.9 to 36 cm) and Gini index (from 0.35 to 0.37 and from 0.33 to 0.36). Pursuant to the Directive 92/43/EEC, the conservation status of these two habitat types should be taken as “favorable” with regards to the criterion related to the habitats’ specific structure and functions that are necessary for its long-term maintenance. We conclude that forest management plans provide a great portion of the information needed for assessing and monitoring the conservation status of forest habitat types in the Natura 2000 framework.